Digital image watermarking using firefly and blowfish algorithms - Narmada, Kari; Kumar, Archek Praveen; Santosh Kumar, Modekurty; Krishnaveni, Adepu; Manasa, Konda (International Journal of Psychosocial Rehabilitation, 2020)
Image is one of the best ways to communicate the message. Many users have secret information to communicate so this privacy is generated by the combined watermarking and cryptography. Firefly and Blowfish algorithms are used to get the optimistic results. The simulation should be suitable for the images we consider. Many researchesprove that watermarking and cryptography are combined but it depends on the images parameters. This paper combines firefly with blowfish algorithms which are simulated in MATLAB to generate promising features. This is simulated with the lighting features of fireflies. Generally fireflies are more attractive to each other in the greater intensity values. Two major processes is considered one is attraction and other is grouping. Factors like SSIM and bit error rates are calculated.